Fault Classification in GCPV Microgrid System Using Wavelet Transform - ZULLKUFFLI, MOHAMAD HAKIMI; binti Mohd Noh, Faridah Hanim (Progress in Engineering Application and Technology, 2024)
Grid-connected photovoltaic (GCPV) microgrids have emerged as a promising alternative to conventional energy sources. To ensure efficient operation, maximum power needs to be extracted from the PV system and 3-phase grid system. PV panels are often connected in series and parallel combinations, forming an array to meet load demands. However, the system can experience various faults, such as grid faults, PV system faults, and grid faults with the PV system in normal conditions, leading to significant reductions in maximum power generation and affecting the load. Wavelet transform techniques are employed to detect damage events by analyzing 3-phase voltage and solar PV array voltage. Wavelet decomposition using 'wavedec' and detailed coefficient extraction using 'detcoef' enable fault classification and identification. The wavelet coefficients can identify all faults, allowing for early isolation of damage locations.